Sex Work, Health, and Human Rights 2021
DOI: 10.1007/978-3-030-64171-9_10
|View full text |Cite
|
Sign up to set email alerts
|

Sex Worker-Led Provision of Services in New Zealand: Optimising Health and Safety in a Decriminalised Context

Abstract: Decriminalisation recognises sex work as work; it provides opportunities for promoting the health of sex workers and therefore goes a long way to addressing health and human rights inequities for this sector of the population. This chapter focuses on three scenarios (among many) where decriminalisation of sex work in New Zealand has been successful in promoting sex workers’ health, safety, and wellbeing and, in so doing, provides a blueprint for best practice in working with sex workers.Although services for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…While such health interventions could work, they need to be coupled with the above discussed legal reforms. Evidence from New Zealand has shown that decriminalisation works in the improvement of the health of sex workers (Abel, 2014;Armstrong, 2014Armstrong, , 2016. Platt et al (2018) also reminds us that sex work is closely linked to poverty, homophobia, and substance abuse, which in turn shape the health and welfare of the sex workers.…”
Section: Discussionmentioning
confidence: 96%
“…While such health interventions could work, they need to be coupled with the above discussed legal reforms. Evidence from New Zealand has shown that decriminalisation works in the improvement of the health of sex workers (Abel, 2014;Armstrong, 2014Armstrong, , 2016. Platt et al (2018) also reminds us that sex work is closely linked to poverty, homophobia, and substance abuse, which in turn shape the health and welfare of the sex workers.…”
Section: Discussionmentioning
confidence: 96%
“…While the Guide assumes equal access to OHS best practices for all sex workers across work environments in NZ, sex work in NZ remains criminalized for im/migrants, limiting access to OHS protections for this population [21]. Research from NZ finds that the "twotiered" approach to decriminalization has restricted applicability of the Guide and thus better working conditions to citizens and residents.…”
Section: Discussionmentioning
confidence: 99%
“…Research from NZ since 2003 has shown that decriminalization has significantly improved OHS conditions and increased access to workplace protections and human rights among sex workers to whom the "Prostitution Reform Act" applies. These positive effects on sex workers' OHS have, however, not been extended to NZ sex workers who are not permanent residents or citizens [21][22][23]. Shortly after the Prostitution Reform Act was passed, the NZ Department of Labour published 'A Guide to Occupational Health and Safety in the New Zealand Sex Industry' (the Guide) [24].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, evidence supports that FOSTA-SESTA, counter to their intent, worsened online sex trafficking and caused substantial harm to online sex workers by removing valuable safety and virtual communication tools shut down by federal policies (Blunt and Wolf 2020). Incorporating community care and harm-reduction principles, SWEI provided community care to de-stigmatize and advocate for the decriminalization of sex work through the centering of sex workers' autonomy and well-being (Abel and Healy 2021;Yandall et al 2021;UTOPIA WA n.d.). The spaces that Guma' Gela' UTOPIA WA create allow QTPI to access community care to promote their health through promoting inágofli'e' and alofa as cultural ways of being and restoring connectedness to culture and community.…”
Section: Facilitating Indigenous Connectedness Through Inágofli'e' An...mentioning
confidence: 99%